Metode Pembelajaran Bahasa Arab - Sam, Zulfiah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2016)
The assembling of learning method will not work eï¬€ectively andefciently as a companion media in learning without a sufcientmethod knowledge. A method of traditional Arabic Learning isan arabic learning method that focused on â€œlanguage as thescientifc traditionâ€ so that learning an arabic means learning anarabic in details, either grammatically/sintactically (QawÄâ€™id alNaá¸¥wu), morpheme/accidence (Qaw á¸¥ Äâ€™id al-á¹¢arf) or literature á¸¥(ÄdÄb). The main aspects in learning arabic are : listening,speaking, reading and writing. The four aspects are mutualrelated, for example, a listening skill contributes to adevelopment of speaking skill, both skills are strengthened byreading skill, while writing skill contributes to a reading skill inthe text or document form. Keyword : Metode, Bahasa Arab.